COMPARATIVE STUDY OF THE EFFICACY OF INTRAVENOUS PARACETAMOL AND DEXMEDETOMIDINE ON POST-OPERATIVE ANALGESIC AND HEMODYNAMICS FOR PATIENTS UNDERGONE UPPER LIMB SURGERY - Parween, Jainab; KHAN, FAHAD (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Comparative study of the efficacy of intravenous paracetamol and dexmedetomidine (DMED) on post-operative analgesic and hemodynamics for patients undergone upper limb surgery. Multimodal analgesia is recommended to reduce the stress response and prevent post-operative pain. Intravenous paracetamol and intravenous DMED are both effective components in respect of multimodal analgesia. Methods: The present prospective randomized, double-blind, controlled study was performed on eighty American Society of Anesthesiologists (ASA) Grade I and Grade II physical status patients aged 18–65 years, of both genders, were selected for elective upper limb orthopedic surgical procedure under general anesthesia. Group P (paracetamol) patients were given 1 g paracetamol intravenously 30 min before surgery. Group D patients, 100 μg DMED/20 mL normal saline, was administered intravenously 30 min before surgery. Post-operative hemodynamic variables, post-operative pain scores (Visual Analogue Scale score), need for rescue analgesics and post-operative complication were recorded and treated accordingly. Results: In both groups, females were in the majority with ASA grade I in the majority of the cases in both groups. Mean heart rate, mean arterial pressure, and Visual Analog Score for pain were comparable between the groups were compared at different time intervals (2, 4, 6, 12, 18, and 24 h) (p>0.05). Regarding complications Nausea, vomiting, itching and stomach irritation was in 17.5%, 15.0%, 7.5% and 20.0% for group D and for group P nausea and vomiting was in 15.0% and 10.0% and no other complication occurs in group D. Conclusion: Pre-emptive administration of paracetamol is a cost-effective and safe method of providing post-operative analgesia for patients undergoing upper limbs surgery.